Profiling of liver transcriptome and fitness-related genes of two trains of Asian catfish (Clarias macrocephalus, Ginther 1864. - Arinez, July B.; Institute of Aquaculture (2020.)
The identification of genetic mechanisms behind the manifestation of desirable traits requires the analysis of gene expression and regulation as indicators of potential physiological performance. In this study, a transcriptome analysis was conducted to identify and compare the expression patterns of various fitness-related genes in the hepatic tissues of two Clarias macrocephalus strains from Cagayan (CmC) and Agusan del Sur (CmA), Philippines. Further comparison of gene expression profiles against a known competitor, Clarias gariepinus (CgC) has also been undertaken to further capture genes underlying robust phenotypic characteristics. By using RNA sequencing, a total of 86,917,741 clean reads were generated nd were de novo assembled into 86,011 unigenes, Functional annotation of the assembled unigenes showed that 61.06% (52,519 unigenes) were successfully annotated using seven public databases. Among the 13, 138 differentially expressed genes (DEGs) identified in CmA vs. CmC, 6,795 DEGs exhibited significant upregulation while 6,343 DEGs displayed significant downregulation. On the other hand, a total of 35,994 and 21,055 DEGs were also found to be significantly upregulated and downregulated in CmA vs. CgC, respectively. From this pool of DEGs, numerous growth- (GLUL, EEF2, GYS, ELOVL6, LPL, CACT), immune- (C3, C4, C7, TFRI, IFI44L) and reproduction- (VTG, CTNNB!, CYP19b, Bambi, PGR) related genes were detected. The significant expression of these genes also corroborated with the results of the pathway enrichment analysis which further revealed the enrichment of the complement component and coagulation cascades, protein digestion and absorption and lipid metabolism pathways. Moreover, microsatellites were also detected in some of the top DEGs. Our study demonstrated that RNA-seq can be used to identify fitness-related DEGs and molecular markers which may help elucidate the underlying genetic mechanisms behind phenotypic variations and physiological vigor between catfish species.
Thesis (Graduate, Master of Science in Fisheries major in Aquaculture) College of Fisheries and Ocean Sciences, University of the Philippines Visayas, 2020.
Keywords: Catfishes -- Asian; Clarias macrocephalus